TINJAUAN HUKUM ISLAM TERHADAP PENITIPAN ORANG TUA OLEH ANAK DI PANTI SOSIAL TRESNA WERDHA SABAI NAN ALUIH SICINCIN KABUPATEN PADANG PARIAMAN - Abdi, Syafral; Bahar, Muchlis (Jurnal AL-AHKAM, 2020)
This study aims to describe the care of parents by children at the Tresna Werdha Social Home (PSTW) Sabai Nan Aluih Sicincin and to review the care of parents by children in social institutions from the perspective of Islamic law. This study uses data collection by interview and observation, as well as supporting documents to be used as references in the preparation of this thesis. The type of research used in this writing is field research and the  approach used in this research  is  normative,  namely  an  approach  to  determine  the  status  of  Islamic  law  in  parental care. The results of this study, there are two reasons why children entrust their parents to PSTW: First,  due  to  the  wishes  of  the  parents  themselves.  Second,  not  because  of  the  parents'  own wishes,  such  as:  not  wanting  to  burden  the  family,  looking  for  friends  and  wanting  to  be  calm, less harmonious, losing roles, neglected at home and economic factors. The reality experienced by parents in the orphanage is divided into two situations. First, parents feel happy. Apart from being  able  to  gather  with  peers,  parents  also  receive  special  care  with  adequate  facilities. Second, parents who do not get happiness, this is because parents do not fit into the environment of the orphanage, and the presence of parents in the orphanage is not of their own accord. Even so,  when  it  is  analyzed  from  a  review  of  Islamic  law,  children  who  leave  their  parents  at  the Tresna  Werdha  Sabai  Nan  Aluih  Sicincin,  Social  Home  are  three  levels  of  law  that  discuss  the law  of  child  care  for  parents  in  PSTW.  If  the  wishes  of  the  parents  themselves,  then  the  law  is makruh,  whereas  if  forced  by  circumstances  the  law  is  permissible,  but  if  children  leave  their parents because they do not want to take care of their parents, while they are self-sufficient, then the law is haram.Keywords: PSTW, Parents, Law, Islam